2005
DOI: 10.1093/humrep/dei013
|View full text |Cite
|
Sign up to set email alerts
|

Clinical adaptation of the sperm ubuquitin tag immunoassay (SUTI): relationship of sperm ubiquitylation with sperm quality in gradient-purified semen samples from 93 men from a general infertility clinic population

Abstract: Use of this simplified ubiquitin-based sperm quality assay is feasible in a clinical environment. Since the gradient separation does not completely deplete the defective spermatozoa, the modified light microscopic sperm ubiquitin tag immunoassay could add a new level of stringency to the selection of human spermatozoa for ICSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 29 publications
0
22
0
1
Order By: Relevance
“…After a 1-h migration, the overlying swim-up sperm were collected, washed twice in Dulbecco's phosphate-buffered saline, and stored at Ϫ20°C. Sperm from a fertile sperm bank donor (Fairfax Cryobank, Fairfax, VA) were washed and used for lectin and antibody binding studies as previously described (18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After a 1-h migration, the overlying swim-up sperm were collected, washed twice in Dulbecco's phosphate-buffered saline, and stored at Ϫ20°C. Sperm from a fertile sperm bank donor (Fairfax Cryobank, Fairfax, VA) were washed and used for lectin and antibody binding studies as previously described (18).…”
Section: Methodsmentioning
confidence: 99%
“…Fixed sperm were incubated overnight at 4°C with anti-Lewis y monoclonal antibody diluted 1:50, washed, and incubated for 40 min at room temperature with a mixture containing the TRITC-conjugated goat anti-mouse IgM (Zymed Laboratories Inc., San Francisco, CA) diluted 1/100. Acrosomal integrity was determined by the addition of fluorescein isothiocyanate-conjugated Arachis hypogaea (peanut) lectin (Sigma) diluted 1/100 into TRITCconjugated goat anti-mouse IgM/4Ј,6-diamidino-2-phenylindole mixture as described previously (18). Coverslips with the processed sperm were mounted on microscopy slides in VectaShield medium (Vector Laboratories, Burlingame, CA) and examined under a Nikon Eclipse 800 microscope (Nikon Inc., Melville, NY) with epifluorescence and differential interference contrast optics and a CoolSnap HQ CCD camera (Roper Scientific, Tucson, AZ) operated by MetaMorph software (Universal Imaging Corp., Downington, PA).…”
Section: Ms and Ms/ms Analyses Of Permethylated Humanmentioning
confidence: 99%
“…Removal of the beads (together with bound cells) would thus yield a theoretically higher quality sample. This would be especially relevant if the defective sperm cells in question could not be identified by simple visualization (1). Indeed, although spermatozoa from patients possess multiple structural and functional defects, usually evaluated by light microscopy (2), this approach can be limited, because, for example, spermatozoa with normal morphology can, nevertheless, have DNA defects or be positive for apoptotic markers (3).…”
mentioning
confidence: 99%
“…This study also demonstrated that ubiquitinated spermatozoa found in the ejaculate, and which may have escaped phagocytosis, are characterized by major defects in the head or axoneme. Furthermore, more recent studies proposed that this biomarker could be used [a] to assess sperm quality by flow cytometry, with poor quality samples yielding higher ubiquitination, which would translate to higher fluorescence intensities (11), and [b] that the assay could also help select spermatozoa for ART, as a complement for classical separations (1). Surprisingly, results obtained by other authors suggest that sperm ubiquitination positively correlates with normal semen parameters in human sperm (especially morphology), thus implying that there may be a functional role for ubiquitination in normal sperm (14).…”
mentioning
confidence: 99%
“…FC technique would be easily coupled with the analysis of spermatozoa extracellular ubiquitination (eUb) level since this indicator was found to be negatively correlated with their fertilization ability (Sutovsky et al 2002;Hodjat et al 2008). The eUb level determination would then improve the quality control in livestock reproduction and clinical medicine (Ozanon et al 2005).…”
Section: Introductionmentioning
confidence: 99%